2018
DOI: 10.1111/jep.13010
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking bias and truth in evidence‐based health care

Abstract: In modern philosophy, the concept of truth has been problematized from different angles, yet in evidence‐based health care (EBHC), it continues to operate hidden and almost undisputed through the linked concept of “bias.” To prevent unwarranted relativism and make better inferences in clinical practice, clinicians may benefit from a closer analysis of existing assumptions about truth, validity, and reality.In this paper, we give a brief overview of several important theories of truth, notably the ideal limit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 55 publications
0
57
0
Order By: Relevance
“…Literature reviews within evidence‐basing is a paradigmatic example of a product shaped by formal rules . The formal rules serve to minimize the influence of personal biases when searching, mapping, and synthesizing scientific studies . Empirical studies of the production of knowledge within STS and other fields, however, have shown that formalized methods help create a canonical view of general and objective scientific knowledge although the actual practices of science are highly particular and informal .…”
Section: Introduction: Evidence‐basing Sts and The Case Of A Scopinmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reviews within evidence‐basing is a paradigmatic example of a product shaped by formal rules . The formal rules serve to minimize the influence of personal biases when searching, mapping, and synthesizing scientific studies . Empirical studies of the production of knowledge within STS and other fields, however, have shown that formalized methods help create a canonical view of general and objective scientific knowledge although the actual practices of science are highly particular and informal .…”
Section: Introduction: Evidence‐basing Sts and The Case Of A Scopinmentioning
confidence: 99%
“…In these recent developments of scoping review methods, the attempts to avoid bias using formal rules assume that individual judgments can be done away with and that the presence of individual judgments would compromise the truth that formal rules aim to establish . However, according to research within STS, formalities do not oppose informal expertise, but they exist in a dynamic and creative interplay .…”
Section: Introduction: Evidence‐basing Sts and The Case Of A Scopinmentioning
confidence: 99%
“…I tried to put Godlee’s article into context because questions arise such as, “What put me in need of drug treatment?” and “Why is this need non-randomly distributed?” I hope we can rethink bias and truth in evidence based healthcare5 and focus our time on other words that start with E 6…”
mentioning
confidence: 99%
“…As reported in the most recent philosophy thematic edition of this journal, researchers are rising to this challenge, to develop accounts of these key ideas with substantive import and application. To do so effectively requires not only extensive empirical work to understand and adequately characterize perspectives previously ignored or marginalized but also a fundamental conceptual shift in our understanding of the nature of and relationships between knowledge, evidence, value, patient experience, and the social context of care, as well as the social context of research and all forms of knowledge production . Put in economic terms, this shift requires a movement away from construing care as something provided to patients by professionals and towards a model of partnership or co‐production: “the design, delivery and evaluation of services in an equal and reciprocal relationship between professionals, people using services, their families and their neighbours.”…”
Section: Introductionmentioning
confidence: 99%